Sub-cellular Proteomics - Nicolas L Taylor (Frontiers Research Topics, 2015)
Whilst significant advances have been made in whole organismal proteomics approaches, many researchers still rely on combinations of tissue selection and subcellular prefractionation methods to reduce the complexity of protein extracts from plants prior to proteomic analysis. Often this will allow identification of many lower abundance proteins of the target proteome and it may involve the selection of specific organs, cell types or the isolation of specific subcellular components. These subcellular proteomes provide insight into functions following various treatments and also contribute to the wider understanding of the entire organismal proteome by cataloguing a series of sub-proteome contents. The aim of this Research Topic is to bring together knowledge of sub cellular components in different plant species to provide a basis for accelerated research. It aims to provide a mini-review for each proposed section that summarizes the current understanding of a particular proteome, with the anticipation that every 5 - 10 years we can update these definitive publications.